Outcomes of a quality improvement project integrating an EHR (electronic health record) for improved adverse drug reaction (ADR) communication at an adult outpatient cancer infusion center. Issue 28 (1st October 2022) - Kollu, Vidya; Letendre, Paul; Oettel, Kurt R.; Markos, Leanne; Srivastava, Piyush
Abstract : 372 Background: An adult oncology practice achieved 41% compliance with communication of ADRs involving infusion drugs to ordering provider during the year 2020. We aim at achieving communication of ADRs to ordering provider with a goal compliance rate of 75% over a period of 8 months. Methods: We assembled an interdisciplinary team comprising of medical oncologists, fellows, clinical nurse managers, infusion & clinic nurses, information technology (IT))providers and a clinical pharmacist. We reviewed ADRs occurring between April-December of 2021 in adult patients receiving outpatient infusion therapy at our institution. We created a current-state process map of ADRs in our infusion center. We identified issues that needed to be addressed including no clear standard for documenting or reporting an infusion reaction, no standard process was in place for proper notification to all parties involved nor was there a consistent location in the EHR regarding the description of events that took place. Acknowledgment by ordering provider to an ADR was used as a primary outcome measure. The RL6 (internal tracking system) patient safety events reported was used as a process measure. PDSA cycle 1 January 2021:We implemented a new flowsheet section in the EHR titled "Adverse Drug Reaction". We created a smart phrase for clarification of documentation, when used will pull information from the flowsheet section into the note. Education was provided to nursing on this new standardized process. Clinicians were educated where to find this information as a standardized location within the EHR. The ordering provider was notified when an ADR occurred by having the infusion nurse document a clinical support note that is routed to the provider's EHR in-basket. PDSA cycle 2 June 2021: Once nursing documented an ADR, an automated message was sent to all the care-team members via the ADR event folder within the EHR in-basket. The nursing staff then would add the ADR orders group to the treatment plan for clinician review. An alert was generated which prompted the clinician to acknowledge the ADR within the Beacon plan thereby alerting the nursing team if any changes were made. Results: In 2021 there were 73 ADR events that have occurred in Infusion Services. Our interventions were associated with an 80% improvement in communication of ADRs to ordering providers and 35% increase in reporting ADR within our internal tracking system. Conclusions: Developing a standardized ADR process enhanced communication of ADRs to the ordering providers as our intervention was associated with an 80% improvement in communication of ADRs over a 8-month period. Involving all major stakeholders, especially the staff working in information technology services, resulted in exponential results demonstrating the potential future solutions within the EHR.